ISLAMIC PHILANTHROPY AND GOVERNMENT POWER: THE DYNAMICS OF THE RELATIONSHIP BETWEEN MOSQUE-BASED ISLAMIC MICROFINANCE COOPERATIVE (BMT) AND THE SOLOK CITY GOVERNMENT - Haris, Gusnam; Billah, Mu'tashim; Rahma, Vivi (Institut Agama Islam Negeri Bone, 2025)
The relationship between government authority and civil society groups (philanthropic institutions) is often dynamic and tends to be imbalanced when one side becomes dominant. Mosque-based BMTs in Solok City show an interesting relationship pattern with the government, particularly before and after the Solok City government received an award. This article examines the pattern of relations between the two using Gretchen Helmke and Steven Levitsky's typology of relations. This field study's data is sourced from interviews with several Solok City officials involved in managing MB-BMT. Data was collected through observation, interviews, and documentation, followed by qualitative analysis. Gretchen Helmke and Steven Levitsky's theory on the typology of relations between the private sector and the state is used to analyze these relations. The results of this study strengthen existing theory, as evidenced by the success of MB-BMT in Solok City, where the relationship between MB-BMT and the Solok City Government is a complementary substitution. The MB-BMT institution aims to strengthen the objectives set by the Solok City Government to protect the community from the clutches of loan sharks by channeling philanthropic funds exclusively through the qardh agreement. Meanwhile, the Solok City Government adopts a passive stance, meaning it grants full autonomy to the mosque institution to manage its operations, resulting in the Solok City Government being ineffective and its role being replaced by the MB-BMT institution. From a management perspective, the MB-BMT in Solok City only performs the functions of a Mal institutional body and does not carry out the tasks of a Tamwil institution. Research shows that when the government is fully involved in the capital and management of MB-BMT institutions, these institutions become inactive and ultimately cease to function.